(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Hair graying is considered as a sign of ageing. In Asians if hair graying occurs before the age of 25 years it is called as premature canities. It is considered as a risk factor for coronary artery disease. It is well-known fact that obesity and hypertension are associated with coronary artery disease. However, the role of obesity in association with premature canities not well known. Hence the present study aims to identify the role of obesity in premature canities. Materials and methods: This cross-sectional study was conducted among the students studying in ACS Medical College and Hospital, Chennai, India. This study was conducted from January 2019 to January 2020. A total of 420 students took part in the present study. Subjects with any known disease were excluded from this study. Subjects with atleast 10 number of gray hairs were considered as cases (n=210) and subjects without gray hair were considered as controls (n=210). Demographic and clinical parameters like age, sex, height, weight, blood pressure, waist circumference and number of gray hairs were collected from the study subjects. P value <0.05 was considered as statistically significant. Statistical analysis was done using SPSS software 20. Results: In our study there is no significant difference in the age of the study subjects (19.1 ±1.4 versus 19.0 ± 0.8 years, P=0.216) respectively. Cases were comparatively obese than controls as measured by BMI (23.5 ± 5.2 vs 21.8 ± 3.2 kg/m2, P= 0.000) and WC (75.5 ± 20.8 vs 63.5 ± 21.0 cm, P=0.000). The prevalence of obesity is 11% (n=24) in subjects with premature canities. The number of subjects with prehypertension more predominant in cases compared with controls (32.8% vs 25.2%) Similarly, cases were predominantly hypertensive compared with controls (8% vs 2.3%) respectively. correlation analysis also showed a significant association between number of gray hairs SBP mmHg (r=0.211) (P=0.002) and BMI (r=0.505) (P=0.000). A significant association between BMI and gray hairs prevailed even after controlling for BP using partial correlation analysis. Discussion & Conclusion: Obesity being a proinflammatory condition plays a key role in the development of hypertension and gray hair through oxidative stress in premature canities.